When making becomes divination: Uncertainty and contingency in computational glitch-events. (November 2015) - Marenko, Betti
Abstract : This article investigates those aspects of computation that concern uncertainty, contingency and indeterminacy. Starting from a critique of current dominant models of computation, and drawing on the philosophical notions of the virtual and the event, uncertainty, contingency and indeterminacy are proposed as virtualities that express the ongoing differentiation of digital matter. On these grounds, the glitch is reframed as an event capable of revealing the potential of the digital in processes of computational making. Ideas concerning the incomputable and non-human intelligence of the algorithm underpin this argument. Finally, it is proposed that intuitive and uncognitive modes of apprehending digital making operate as forms of divination that capture the unprogrammed unfolding of matter. Highlights: The glitch is the tangible evidence of the autonomous capacities of digital matter. The digital is recognized as affording and manifesting an ongoing differentiation. Computational making is proposed as an uncertainty-driven process. Digital algorithms are modes of thought with autonomous design potential. Risk-driven precise indeterminacy is a resource questioning design determinism.